2016
DOI: 10.1097/md.0000000000002308
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Versus Oral Iron for the Treatment of Anemia in Inflammatory Bowel Disease

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
91
1
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(108 citation statements)
references
References 40 publications
3
91
1
13
Order By: Relevance
“…Other feature that has negatively influenced the option of treatment with oral iron is the putative reported increased prevalence of intestinal adenomas associated to prolonged oral iron treatment, in murine colitis model [30,32,33]. However, the true impact of oral iron on mucosal injury in IBD patients is not well established and the potential risk of colorectal carcinoma in humans remains controversial [36].…”
Section: Current Topics In Anemiamentioning
confidence: 99%
See 3 more Smart Citations
“…Other feature that has negatively influenced the option of treatment with oral iron is the putative reported increased prevalence of intestinal adenomas associated to prolonged oral iron treatment, in murine colitis model [30,32,33]. However, the true impact of oral iron on mucosal injury in IBD patients is not well established and the potential risk of colorectal carcinoma in humans remains controversial [36].…”
Section: Current Topics In Anemiamentioning
confidence: 99%
“…However, evidence regarding the superiority of IV iron versus oral formulas is yet to be proven [30][31][32][33]. In fact, there are several studies and systematic reviews comparing oral and different IV formulas, with variable results considering efficacy in improving Hb levels, tolerance, and safety (related to common severe adverse effects) [4,6].…”
Section: Efficacy Safety and Tolerance Datamentioning
confidence: 99%
See 2 more Smart Citations
“…In a recently published meta-analysis by Bonovas et al (25), integrated evidence from randomized controlled trials showed that IV administration of iron is more effective than oral iron uptake in achieving hemoglobin rise of ≥2.0 g/dL, and it is better tolerated as compared to oral iron in IBD. In another metaanalysis by Tolkien et al (26) oral iron (ferrous sulfate) resulted in remarkable GI side effects in adults when compared to either placebo or IV iron.…”
Section: Treatment Of Anemia Due To Ibd and Gi Hemorrhagementioning
confidence: 99%